(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To assess the integrated modular system of teaching of Karachi Medical and Dental College. Methods: This cross-sectional study was y conducted in Karachi Medical and Dental College from 1st May 2021 to 31st May 2021.Data was collected from first year and second year MBBS students of Karachi Medical and Dental college through a self-administered questionnaire which contained variable regarding participant’s demographics, their views regarding various modes of teaching and different aspects of integrated system of teaching by using a 5 point Likert scale. The questionnaire was validated through a pilot study. Results: The questionnaires were filled by 215 students. Some students (48.4%, n=104) found lectures a little useful. Majority(58.6%,n=126) students were of the opinion that tutorials were not useful. About 99(46.0%) students agreed that the curriculum taught was at the level of their understanding. A large number 104(48.4%) of students agreed that it helped them understanding topics. Most(51.6%,n=111) were not satisfied with the time allocation for module completion. Conclusion: Majority of the students were satisfied with the curriculum but were not satisfied with the time allocation for each module. Modular system of teaching also helped students in better learning of pathologies.